A Novel Robotic Arm Design for Small Scale Industries Using myRIO - Srilatha, M.; Hemalatha, R. (International Journal of Engineering and Technology, 2018)
In small-scale industries, under extreme working conditions, personnel are frequently involved in lifting and carrying raw materials, which is hazardous at times. Robot, a machine with intelligence can perform the same task with the help of control instructions fed by computer or remote control. Technological development in the area of robotics made it possible to design robotic arm with the same degree of precision as a replacement to the human intervention. This will introduce automation in small-scale industries, which saves time, reduces human effort and expenditure in production. Further, this will be a starting point for complete automation of entire process, which can be expensive and complicated. NI LabVIEW along with NI-myRIO can provide a better solution in designing a more precise and accurate robot in a very low cost, which is affordable by small-scale industries. NI-myRIO is used to generate and acquire signals for controlling and processing. Further it has an inbuilt processor and FPGA which has many reconfigurable analogue and digital features.Â Â